uPark: a progressive web parking application - Panos, Konstantinos; Papaioannou, Evi; Kaklamanis, Christos (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
We present uPark, a progressive web parking application for the online purchase of slots of pre-paid parking time, which remains associated to client accounts rather than bounded to particular parking spots or vehicles. uPark integrates three sub-systems, one for drivers, one for inspectors and one for administrators. It optimizes the overall parking process for citizens/clients from a financial and a practical point of view and technically facilitates the work of inspectors. It is a lightweight, easy-to-use, responsive application. Moreover, as a progressive web application, uPark can be used both as a web site and a mobile app on any device. uPark can be used for various areas, like city center, mall parking area or university campus, making a time- and effort-saving, eco-friendly and useful progressive web application.